Abiguitas Regulasi Sunat Perempuan di Indonesia: Analisis Bipolitik atas Peran Negara - Aziza Nawra Pasya; Rachel Aulia; Ika Arinia Indriyany (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The practice of female genital mutilation is still found in various regions of Indonesia and is often viewed as part of cultural traditions or religious practices. However, this practice has also sparked debate because it is considered to have no medical benefits and to potentially endanger women’s health and bodily autonomy. This study aims to analyze the ambiguity of state regulations regarding the practice of female genital mutilation in Indonesia through a biopolitical perspective. This study employs a qualitative descriptive method using a literature review approach, drawing from academic journals, books, and government policy documents. The results indicate that state policies regarding female circumcision exhibit inconsistent regulatory dynamics, marked by the implementation of medical guidelines through a Ministry of Health regulation in 2010, which was subsequently revoked in 2014. This situation highlights the state’s ambiguous position in balancing the protection of women’s health with the pressures of cultural and religious norms within society.